Physiological response to sub lethal concentration of nickel on marine and fresh water algae - Manju, M R; Balakrishnan, K P (Indian Journal of Fisheries, 2011)
Effect of nickel at low levels on chlorophycean alga and a diatom was studied. Acomparative study of the growth parameters made on both the microalgae showedthat divalent nickel retarded the growth of algae at the higher concentration usedeven though low test concentrations had a stimulatory effect. It was found thatnickel toxicity is related to the presence of divalent nickel and can be influencedby environmental factors.